Fermented black rice bran extract inhibit colon cancer proliferation in WiDr cell lines - SAFRIDA, (2022)
Abstract The objective of this study was to find the best inhibition of WiDr colon cancer cells growth using Fermented Black Rice Bran (FBRB) extract and the mechanism of colon cancer inhibition by fermented rice bran. In this study, BRB was fermented by Rhizopus oligosporus (FBROLI), Rhizopus oryzae (FBRO), respectively, for 0, 24, 48, 72, and 96 h to analyze changes profile of phenolic content, total flavonoid, and antioxidant activity during fermentation. The result of elected fermentation and non-fermented (0 h) (NFBR) analyzed cytotoxic activity on Vero normal cells and WiDr cells. Genes’ mRNA expression of proliferation and apoptotic markers on WiDr cells was also analyzed that normalized the ACTB housekeeping gene. The results demonstrated that fermentation for 72 h produced the highest phenolic content, total flavonoids, and antioxidants activity with FBROLI extract, which had the highest inhibition of WiDr cells with IC50 value 650.7 μg/mL, while the FBRO with IC50 was 873.9 μg/mL, and NFBR with IC50 was 831.8 μg/mL. The mechanism of inhibition of WiDr cells through suppression of PCNA proliferation gene expression and increased apoptotic gene expression of p53, caspase-8, caspase-9, and caspase-7 with the highest increase of apoptotic gene expression obtained FBROLI extracts.